DAMPAK PERKEMBANGAN INFRASTRUKTUR PARIWISATA TERHADAP KONFLIK AIR DI KABUPATEN BADUNG DAN TABANAN - Trisnawati, Hikmah (Jurnal Ilmiah Pariwisata; Volume 2 No.1 Hal 109-222 September 2012, 2012)
Water is an important source for life in the world. If we lost it, many problems will arise. The location of this research is in Kerobokan area, Badung Regency, and some areas of Tabanan Regency. This research was done by observing and interviewing about 41 people, consisting of Villa’s, Hotels and Restaurants owner (investor), domestic and international tourists, staff of PDAM and Government, and farmers. This research was conducted from January- February 2011, with some students from IREST Paris 1 Pantheon-Sorbonne and some students from Udayana University. From the data of this study, then Tabanan and Badung were being compared, so it can be seen the similarities and differences in water issues that occur in each region. Then, the development of the infrastructure has reduced the farming field and in Tabanan, in dry season, water can be a serious problem. The actors in that conflict are between farmers, between farmers and Government (PDAM), and between farmers and investors (Villas, Hotels and Restaurants owner). The type of the conflict in Tabanan and Badung is the lack of water and water pollution.
Keywords: Water conflict, Infrastructure, lack of water and water pollution